A hardware system with ARM-based data processing for nano satellites - Adrián Stacul; Daniel Pastafiglia; Ariel Di Giovanni; Martín Morales; Sergio Saluzzi; Gerardo García; Agustín Gadea; Ramiro Puga (International Journal of Reconfigurable and Embedded Systems (IJRES), 2020)
The Institute of Scientiﬁc and Technical Research for Defense in Argentina (Instituto de Investigaciones Cientíﬁcas y Técnicas para la Defensa - CITEDEF) is developing a processing hardware module based on a ARM Cortex M4 processor from STMicroelectronics. The microcontroller (MCU) has the capacity to run at a maximum clock frequency of 180 MHz, integrates a Floating Point Unit (FPU). An 8MB SDRAM was included for dynamic data allocation. This hardware will host and process the algorithms to calculate and determine the nanosatellite’s attitude. The module is intended to be Cubesat compatible, possess a ﬂexible design, handles various inertial sensors and can manage backups on microSD memory cards with sizes up to 32GB.